EXPLORING THE ECOSYSTEM OF DIGITAL ENTREPRENEURSHIP - MITRACHE DANIEL MARIUS; SPULBAR LUCIAN FLORIN; SMARANDESCU ANDREI (Analele Universităţii Constantin Brâncuşi din Târgu Jiu : Seria Economie)
The digital entrepreneurship ecosystem has emerged as a transformative paradigm, reshaping traditional business structures and fostering a digitally-centric economy. This study examines the intricate dynamics within digital entrepreneurship by exploring the intersection of technological innovation, market fluidity, and entrepreneurial adaptability. Digital entrepreneurship extends beyond conventional models, requiring entrepreneurs to engage with sophisticated digital tools, platforms, and data-driven strategies. By drawing on theoretical frameworks from innovation studies, platform economics, and ecosystem theory, this paper aims to delineate the critical elements that define and sustain digital entrepreneurial ventures. The analysis addresses how digital entrepreneurship not only capitalizes on technology but also navigates unique challenges, such as heightened competition, data privacy concerns, and the accelerated pace of digital transformation. Additionally, the study highlights the role of supportive ecosystems—comprising venture capital, regulatory bodies, and digital infrastructure—in facilitating sustainable digital ventures. Through an integrative approach, the research emphasizes the need for a holistic understanding of digital entrepreneurship, considering both the micro-level decisions of entrepreneurs and the macro-level impacts of digital transformation on economic development. Ultimately, this paper contributes to the growing body of knowledge on digital entrepreneurship by outlining strategic implications for aspiring digital entrepreneurs and policy recommendations for fostering a resilient digital economy.